2016
DOI: 10.1121/1.4968781
|View full text |Cite
|
Sign up to set email alerts
|

Effects of age and hearing loss on concurrent vowel identification

Abstract: Differences in formant frequencies and fundamental frequencies (F0) are important cues for segregating and identifying two simultaneous vowels. This study assessed age- and hearing-loss-related changes in the use of these cues for recognition of one or both vowels in a pair and determined differences related to vowel identity and specific vowel pairings. Younger adults with normal hearing, older adults with normal hearing, and older adults with hearing loss listened to different-vowel and identical-vowel pairs… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

3
9
0

Year Published

2017
2017
2021
2021

Publication Types

Select...
4
2

Relationship

1
5

Authors

Journals

citations
Cited by 18 publications
(12 citation statements)
references
References 47 publications
3
9
0
Order By: Relevance
“…The effects of F0 on concurrent vowel identification were comparable and consistent with previous data (Arehart et al, 1997; Bidelman and Yellamsetty, 2017; Chintanpalli and Heinz, 2013; Chintanpalli et al, 2016; Reinke et al, 2003; Yellamsetty and Bidelman, 2018), listeners were better at perceptually identifying speech mixtures when vowels contained pitch cues. However, we also showed that this perceptual F0-benefit was larger for the clean than the noise degraded (+5 dB SNR) conditions.…”
Section: Discussionsupporting
confidence: 89%
See 3 more Smart Citations
“…The effects of F0 on concurrent vowel identification were comparable and consistent with previous data (Arehart et al, 1997; Bidelman and Yellamsetty, 2017; Chintanpalli and Heinz, 2013; Chintanpalli et al, 2016; Reinke et al, 2003; Yellamsetty and Bidelman, 2018), listeners were better at perceptually identifying speech mixtures when vowels contained pitch cues. However, we also showed that this perceptual F0-benefit was larger for the clean than the noise degraded (+5 dB SNR) conditions.…”
Section: Discussionsupporting
confidence: 89%
“…A handful of studies have shown certain vowels dominate perception among different vowel pair combinations (Assmann and Summerfield 1990; Assmann and Summerfield, 2004; Chintanpalli et al, 2014; Chintanpalli and Heinz, 2013; Chintanpalli et al, 2016; Meddis and Hewitt, 1992a), reminiscent of our vowel dominancy data (Fig. 6).…”
Section: Discussionsupporting
confidence: 72%
See 2 more Smart Citations
“…The task of the listener is to identify both vowels, and performance is measured as a function of F0 difference between the two vowels. For YNH listeners, identification scores for both vowels improve as F0 difference increases between the two vowels, and then asymptotes usually at $3-Hz F0 difference or higher (Assmann and Summerfield, 1990;Summerfield and Assmann, 1991;Culling and Darwin, 1993;Arehart et al, 1997Arehart et al, , 2005Summers and Leek, 1998;Vongpaisal and Pichora-Fuller, 2007;Chintanpalli and Heinz, 2013;Chintanpalli et al, 2016). However, these studies have been typically conducted at a single vowel level.…”
Section: Introductionmentioning
confidence: 99%